STRATEGI PENGUATAN DAYA SAING PESANTREN DI ERA DIGITAL - Saputra, Darwin Eka; Sirozi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the digital era, Islamic boarding schools (pesantren) are undergoing significant changes in their educational system, particularly in integrating traditional pesantren curricula with formal state education. Some pesantren choose to maintain traditional practices, while others transform into modern pesantren by adopting technology and science-based curricula without abandoning traditional values. This study aims to explore the dynamics of pesantren transformation in the face of digitalization challenges and the implementation of Law No. 18 of 2019 on Pesantren. A qualitative approach with content and descriptive analysis was used. Data were obtained from literature, including journals, books, theses, and relevant documents related to the educational traditions of pesantren and the development of digitalization. The findings indicate that pesantren, as religious-based educational institutions, now face significant challenges in integrating technology without losing the Islamic values that characterize them. Traditional pesantren, which still maintain old methods, must adapt to the demands of the times, while modern pesantren have implemented technology in teaching, such as e-learning and social media, to expand access to knowledge. In facing the digital era, pesantren are also required to strengthen human resource capacity, develop quality digital content, and establish collaborations with digital education institutions to enrich the learning experience of their students. External challenges, such as the influence of materialistic culture, technological developments, and changes in social systems, also affect the existence of pesantren in the globalized era. This study recommends the importance of pesantren building digital literacy and producing moderate and tolerant Islamic literature through the use of technology.